Role of microRNAs in the resistance of prostate cancer to docetaxel and paclitaxel - Kopczyńska, Ewa (Contemporary Oncology/Współczesna Onkologia, 2015)
Taxanes, a group of cancer drugs that includes docetaxel and paclitaxel, have become a front-line therapy for a variety of metastatic cancers, but resistance can develop. There are several docetaxel resistance mechanisms in prostate cancer: unfavorable tumor microenvironment, drug efflux pump, alterations in microtubule structure and/or function, and apoptotic defects (e.g. up regulation of Bcl-2 and clusterin or activation of the PTEN/PI3K/mTOR pathway or activation of the MAPK/ERK pathway). MicroRNAs (miRNAs), small regulatory molecules, could also function as a contributor to the resistance of cancer cells to commonly used anti-cancer drugs. Aberrant expressions of miRNAs that can act as tumor suppressors or oncogenes are closely associated with the development, invasion and metastasis of various cancers including prostate cancer. Nearly 50 miRNAs have been reported to be differentially expressed in human prostate cancer so far, but knowledge concerning the effects of miRNAs on the sensitivity to anti-cancer drugs is still limited. The author of the review focus on probable impact of miRNAs on the resistance to docetaxel and paclitaxel. Overexpression of miR-21 increased the resistance of prostate cancer cells to docetaxel by targeting PDCD4, PTEN, RECK, and BTG2. Nevertheless, decreased expressions of tumor suppressors: miR-34a, miR-143, miR-148a and miR-200 family are involved in resistance of anti-cancer drugs by inhibition of apoptosis and activation of signaling pathways. Conclude miRNAs become very attractive target for potential therapeutic interventions.